Morphology and morphometric of Tetragonula biroi bees at three different altitudes in South Sulawesi, Indonesia - ANDI PRASTIYO; SITTI NURAENI; BUDIAMAN BUDIAMAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Prastiyo A, Nuraeni S, Budiaman. 2024. Morphology and morphometric of Tetragonula biroi bees at three different altitudes in South Sulawesi, Indonesia. Biodiversitas 25: 1993-2002. Tetragonula biroi Friese 1898 is a stingless bee species that plays an essential role in pollination and environmental conservation. This research is important because bees play a crucial role as pollinators for the sustainability of plants, and morphometric measurements can reveal patterns of adaptation and the potential production of products generated by these bees. This research aims to analyze the morphological and morphometric variations of T. biroi at three different altitudes in South Sulawesi. The study was conducted from November 2023 to January 2024, with sampling points in lowland (158 meters above sea level or masl), midland (417 masl), and highland (709 masl), using Principal Component Analysis (PCA) test using XLSTAT and one-way analysis of variance (ANOVA) test using program SPSS. Observations of T. biroi morphology at the three locations were generally similar, with a black body color tinged with brown and characteristic hamuli numbering five. The morphometric analysis involved measuring body dimensions of T. biroi across 35 characters/sections of the external body, and the one-way ANOVA test results showed that the dominant characters significantly influencing were body length (BL) and length of fore wing, including tegula (WL1). T. biroi bees at lowlands tend to have smaller bodies, measuring 3.73±0.09 mm, while those at higher altitudes tend to have larger bodies, measuring 4.09±0.14 mm. This indicates adaptation to environmental conditions such as temperature (26.75C), humidity (81%), and dominant vegetation (Cocos nucifera L.) in lowland, which influence bee adaptation, as well as in midland and highland areas. This research provides a better understanding of morphological and morphometric variations in T. biroi bees at various altitudes in South Sulawesi. The morphology and morphometrics description of bees is crucial in determining the growth and production of a species.